Pinning effects on flux flow instability in epitaxial Nb thin films. (27th June 2017) - Dobrovolskiy, Oleksandr V; Shklovskij, Valerij A; Hanefeld, Marc; Zörb, Markus; Köhs, Lukas; Huth, Michael
Abstract: The flux flow properties of epitaxial niobium films with different pinning strengths are investigated by dc electrical resistance measurements and mapped to results derived within the framework of a theoretical model. The cases of weak random pinning in as-grown films, strong random pinning in Ga ion-irradiated films, and strong periodic pinning induced by a nanogroove array milled by a focused ion beam are investigated. The generic feature of the current–voltage curves of the films consists of instability jumps to the normal state at some instability current density j * as the vortex lattice reaches its critical velocity v * . While v * ( B ) monotonically decreases for as-grown films, the irradiated films exhibit a non-monotonic dependence v * ( B ) attaining a maximum in the low-field range. In the case of nanopatterned films, this broad maximum is accompanied by a much sharper maximum in both v * ( B ) and j * ( B ), which we attribute to the commensurability effect when the spacing between the vortex rows coincides with the location of the grooves. We argue that the observed behavior of v * ( B ) can be explained by the pinning effect on the vortex flow instability and support our claims by fitting the experimental data to theoretical expressions derived within a model accounting for the field dependence of the depinning current density.